Acute pesticide poisoning and its relationship with intentionality in patients from a hospital in Ibague-Colombia - Guerra-Rodríguez, Nelson; Sierra-Ramírez, Erika; Jiménez-León, Jackson; Rodríguez-Ospina, Fabio León (Universidad y Salud, 2020)
Introduction: Acute pesticide poisoning associated with suicide is a public health problem that requires special attention by state agencies. Objective: To establish the relationship of patient’s intent with acute pesticide poisoning and describe some sociodemographic and exposure characteristics registered by a hospital in Ibagué (Colombia), from 2013 to 2016. Materials and methods: A retrospective, cross-sectional, descriptive, observational study was conducted on 137 reports of acute pesticide poisoning that were registered according to ICD 10 codes. A descriptive and stratified statistical analysis was applied to establish the association between characteristics of poisoning intentionality. Results: 50% of the cases corresponded to people who were under 20 years of age. 79.6% of the poisonings were due to suicide attempt and 45% had had a previous attempt. A high educational level corresponded to a lower risk of intentional poisoning (OR 0.05; IC 95% 0.01-0.56; p=0.01). Conclusions: Cooperation between health care authorities and public institutions is necessary to implement measures and strategies in order to prevent acute pesticide poisoning events, especially those associated with suicide attempts, the frequency of which is growing in this city.